Organic silicon heat conduction material and optical module

By using specially made silicone thermal conductivity materials in the optical module, the problem of irrational thermal conductivity and overflow rate of thermal interface materials in the prior art is solved, efficient thermal management is achieved, and the heat dissipation performance of the optical module is improved.

CN119799008APending Publication Date: 2025-04-11SHENZHEN XINQUAN SEMICON MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411993913.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The thermal interface materials used in existing optical modules have problems with irrational thermal conductivity and overflow rates, resulting in poor thermal management results.

Method used

A silicone thermal conductivity material is used, which consists of a silicone resin matrix and a thermal filler. The thermal filler includes a variety of thermal conductivity fillers of different particle sizes. Through a specific particle size ratio and composition ratio, the thermal conductivity performance is improved and the overflow rate is reduced.

Benefits of technology

A high thermal conductivity coefficient (greater than 10W/m.K) and low overflow rate (greater than 0.1%) are achieved, while a high dispensing amount (greater than 60g/min) is maintained, which improves the heat dissipation effect of the optical module.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799008A_ABST
    Figure CN119799008A_ABST
Patent Text Reader

Abstract

The invention discloses an organic silicon heat conduction material and an optical module. The organic silicon heat-conducting material comprises a silicon resin matrix and a heat-conducting filler, the heat-conducting filler comprises a first heat-conducting filler, a second heat-conducting filler, a third heat-conducting filler and a fourth heat-conducting filler; according to the mass ratio, the heat conduction filler accounts for 90% or above of the organic silicon heat conduction material, and the first heat conduction filler accounts for 30%-65% of the organic silicon heat conduction material; the second heat-conducting filler accounts for 5-55% of the organic silicon heat-conducting material; the third heat-conducting filler accounts for 1-30% of the organic silicon heat-conducting material; the fourth heat-conducting filler accounts for 0.1-2% of the organic silicon heat-conducting material; wherein the D50 particle size of the first heat conducting filler is 50.5 microns to 100 microns; the D50 particle size of the second heat-conducting filler is 10.5-50 microns; the D50 particle size of the third heat-conducting filler is 0.1-10 microns; and the D50 particle size of the fourth heat-conducting filler is 100 nanometers or less. The organic silicon heat conduction material provided by the invention has high heat conductivity and low overflow rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of heat conduction technology, and in particular to an organic silicon heat conducting material and an optical module. Background Art

[0002] With the rapid development of emerging technologies such as artificial intelligence, big data, the Internet of Things, and cloud computing, the importance of optical modules as core equipment in optical communication systems has become increasingly prominent. Optical modules are not only widely used in the telecommunications market (base stations) and data centers, but also show great potential in automotive electronics, medical and other fields. Optical modules, whose full name is optical transceiver integrated module, are one of the core accessories in network communication, mainly completing the conversion between optical signals and electrical signals. Optical modules are composed of optoelectronic devices, functional circuits, and optical interfaces. The optoelectronic devices include two parts: transmitting and receiving. The transmitting part converts the electrical signal into an optical signal, and the receiving part converts the optical signal into an electrical signal. With the exponential growth of data traffic, the integration of components and power consumption are getting higher and higher, and thermal design and thermal management have become the most critical issues for optical modules. By filling thermal interface materials, the heat in the module is quickly and efficiently transferred to the heat conduction of the metal shell, which is the main way to achieve internal heat dissipation of optical modules. Considering that the overflow of small molecules such as siloxane under long-term working conditions will cause the performance of optical modules, especially optical devices, to deteriorate, the thermal interface materials used for optical modules must have characteristics such as high thermal conductivity and low overflow.

[0003] In related technologies, in order to achieve high thermal conductivity, it is often necessary to add a high content of thermal conductive powder and use low viscosity polymers such as silicone. However, low viscosity silicone often has high chain movement ability and is easy to overflow from the thermal interface material, resulting in an increase in the overflow rate of the thermal interface material. The thermal interface material has both high thermal conductivity and low overflow rate, which has always been a technical challenge for thermal interface materials used in optical module heat dissipation. Summary of the invention

[0004] In view of this, the present application provides a silicone thermally conductive material and an optical module, aiming to improve the problem of irrational thermal conductivity and overflow rate of existing thermally conductive materials.

[0005] In a first aspect, an embodiment of the present application provides an organic silicon thermal conductive material, wherein the organic silicon thermal conductive material comprises a silicone resin matrix and a thermal conductive filler;

[0006] The thermally conductive filler comprises a first thermally conductive filler, a second thermally conductive filler, a third thermally conductive filler and a fourth thermally conductive filler; calculated by mass ratio, the thermally conductive filler accounts for more than 90% of the organic silicon thermally conductive material, the first thermally conductive filler accounts for 30% to 65% of the organic silicon thermally conductive material; the second thermally conductive filler accounts for 5% to 55% of the organic silicon thermally conductive material; the third thermally conductive filler accounts for 1% to 30% of the organic silicon thermally conductive material; the fourth thermally conductive filler accounts for 0.1% to 2% of the organic silicon thermally conductive material;

[0007] Among them, the D50 particle size of the first thermally conductive filler is 50.5 microns to 100 microns; the D50 particle size of the second thermally conductive filler is 10.5 microns to 50 microns; the D50 particle size of the third thermally conductive filler is 0.1 microns to 10 microns; and the D50 particle size of the fourth thermally conductive filler is 100 nanometers or less.

[0008] In some embodiments of the present application, the thermally conductive filler accounts for 94% to 97% of the organic silicon thermally conductive material; and / or

[0009] The first thermally conductive filler accounts for 35% to 60% of the organic silicon thermally conductive material; the second thermally conductive filler accounts for 10% to 50% of the organic silicon thermally conductive material; the third thermally conductive filler accounts for 5% to 20% of the organic silicon thermally conductive material; and the fourth thermally conductive filler accounts for 0.1% to 1.4% of the organic silicon thermally conductive material.

[0010] In some embodiments of the present application, the first thermally conductive filler, the second thermally conductive filler, the third thermally conductive filler and the fourth thermally conductive filler are independently selected from one or more of aluminum oxide, aluminum nitride, silicon oxide, zinc oxide, boron nitride and diamond.

[0011] In some embodiments of the present application, the first thermally conductive filler, the second thermally conductive filler, the third thermally conductive filler, and the fourth thermally conductive filler are independently spherical or angular.

[0012] In some embodiments of the present application, the thermally conductive filler consists of the first thermally conductive filler, the second thermally conductive filler, the third thermally conductive filler and the fourth thermally conductive filler.

[0013] In some embodiments of the present application, the silicone resin matrix includes polydimethylsiloxane having a long-chain branched structure; or

[0014] The silicone resin matrix includes vinyl terminated polydimethylpolysiloxane, side chain silicon-hydrogen bonded polydimethylpolysiloxane and silicon-hydrogen terminated polydimethylpolysiloxane; and / or

[0015] The organic silicon thermally conductive material further comprises at least one of a filler modifier, a catalyst, and an inhibitor; and / or

[0016] The dispensing amount of the organic silicon thermal conductive material is greater than or equal to 60g / min; and / or

[0017] The thermal conductivity of the organic silicon thermally conductive material is greater than or equal to 10 W / mK; and / or

[0018] The overflow rate of the organic silicon thermal conductive material is less than or equal to 0.1%.

[0019] In some embodiments of the present application, the viscosity of the vinyl-terminated polydimethylpolysiloxane is 50 to 500 mPa.s, and the terminal vinyl content in the vinyl-terminated polydimethylsiloxane is 0.5%-2%; and / or

[0020] The viscosity of the silicon-hydrogen terminated polydimethylpolysiloxane is 10 to 100 mPa.s, and the content of silicon-hydrogen bonds in the silicon-hydrogen terminated polydimethylpolysiloxane is 0.1% to 3.0%; and / or

[0021] The viscosity of the polydimethylpolysiloxane with side chain silicon-hydrogen bonds is 10 to 100 mPa.s, and the content of silicon-hydrogen bonds in the polydimethylpolysiloxane with side chain silicon-hydrogen bonds is 0.1% to 3.0%; and / or

[0022] Calculated by mass ratio, the vinyl-terminated polydimethylpolysiloxane accounts for 1% to 3% of the silicone thermal conductive material; the silicon-hydrogen-terminated polydimethylpolysiloxane accounts for 0.2% to 1.5% of the silicone thermal conductive material; and the side chain silicon-hydrogen bonded polydimethylpolysiloxane accounts for 0.5% to 2% of the silicone thermal conductive material.

[0023] In some embodiments of the present application, the filler modifier includes an alkyltrialkoxysilane coupling agent; and / or

[0024] The catalyst comprises at least one of a Spier catalyst and a Custer catalyst; and / or

[0025] The mass percentage of the catalyst in the organic silicon thermal conductive material is 0.1% to 2%; and / or

[0026] The inhibitor comprises at least one of acetylene compounds, ene-yne ​​compounds, and methylvinylcyclosiloxane; and / or

[0027] The inhibitor accounts for 0.1% to 0.5% by mass of the organic silicon thermal conductive material; and / or

[0028] The filler modifier accounts for 1% to 5% of the mass of the organic silicon thermal conductive material.

[0029] A second aspect of the present application provides an optical module, wherein the optical module includes the organic silicon thermal conductive material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0031] Figure 1 Schematic diagram of the organic silicon thermal conductive material in the embodiment of the present application. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0034] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0035] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0036] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0037] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0038] With the rapid development of emerging technologies such as artificial intelligence, big data, the Internet of Things, and cloud computing, the importance of optical modules as core equipment in optical communication systems has become increasingly prominent. Optical modules are not only widely used in the telecommunications market (base stations) and data centers, but also show great potential in automotive electronics, medical and other fields. Optical modules, whose full name is optical transceiver integrated module, are one of the core accessories in network communication, mainly completing the conversion between optical signals and electrical signals. Optical modules are composed of optoelectronic devices, functional circuits, and optical interfaces. The optoelectronic devices include two parts: transmitting and receiving. The transmitting part converts the electrical signal into an optical signal, and the receiving part converts the optical signal into an electrical signal. With the exponential growth of data traffic, the integration of components and power consumption are getting higher and higher, and thermal design and thermal management have become the most critical issues for optical modules. By filling thermal interface materials, the heat in the module is quickly and efficiently transferred to the heat conduction of the metal shell, which is the main way to achieve internal heat dissipation of optical modules. Considering that the overflow of small molecules such as siloxane under long-term working conditions will cause the performance of optical modules, especially optical devices, to deteriorate, the thermal interface materials used for optical modules must have characteristics such as high thermal conductivity and low overflow.

[0039] In related technologies, in order to achieve high thermal conductivity, it is often necessary to add a high content of thermal conductive powder and use low viscosity polymers, such as silicone resin. However, low viscosity silicone resins often have high chain movement ability and are easy to overflow from the thermal interface material, resulting in an increase in the overflow rate of the thermal interface material. The thermal interface material has both high thermal conductivity and low overflow rate, which has always been a technical challenge for thermal interface materials used in optical module heat dissipation.

[0040] In view of this, an embodiment of the present application provides a silicone thermally conductive material to solve the problem of a high overflow rate of existing composite materials based on silicone resin.

[0041] The organic silicon thermal conductive material provided in the embodiment of the present application includes a silicone resin matrix and a thermal conductive filler; the thermal conductive filler includes a first thermal conductive filler, a second thermal conductive filler, a third thermal conductive filler and a fourth thermal conductive filler; the D50 particle size of the first thermal conductive filler is 50.5 microns to 100 microns; the D50 particle size of the second thermal conductive filler is 10.5 microns to 50 microns; the D50 particle size of the third thermal conductive filler is 0.1 microns to 10 microns; the D50 particle size of the fourth thermal conductive filler is 100 nanometers and below; calculated by mass ratio, the thermal conductive filler accounts for more than 90% of the organic silicon thermal conductive material, the first thermal conductive filler accounts for 30% to 65% of the organic silicon thermal conductive material; the second thermal conductive filler accounts for 5% to 55% of the organic silicon thermal conductive material; the third thermal conductive filler accounts for 1% to 30% of the organic silicon thermal conductive material; the fourth thermal conductive filler accounts for 0.1% to 2% of the organic silicon thermal conductive material.

[0042] In this embodiment, a thermally conductive filler is added to the silicone resin matrix, and the thermally conductive filler includes a first thermally conductive filler, a second thermally conductive filler, a third thermally conductive filler and a fourth thermally conductive filler. The first thermally conductive filler, the second thermally conductive filler, the third thermally conductive filler and the fourth thermally conductive filler of a specific particle size are compounded to make the filling ratio of the thermally conductive filler in the organic silicon thermal conductive material greater than 90%, so that the organic silicon thermal conductive material in this application has a higher thermal conductivity. At the same time, since the organic silicon thermal conductive material also includes 0.1% to 2% of the fourth thermally conductive filler with a particle size less than 100 nanometers, the fourth thermally conductive filler with a smaller particle size can be filled between two fillers of large particles, which can greatly reduce the distance between fillers in the organic silicon thermal conductive material, and can make the distance between fillers close to or less than the size of the molecular chain in the organic silicon resin matrix, thereby producing a confinement effect, reducing the kinetic energy of the organic silicon resin, and helping to reduce the overflow rate of the organic silicon thermal conductive material in this application. At the same time, the fourth thermally conductive filler with a smaller particle size can be filled between the two fillers with larger particles, which can further increase the proportion of the thermally conductive filler in the silicone resin matrix, and is beneficial to improving the thermal conductivity of the organic silicon thermally conductive material.

[0043] Exemplarily, the D50 particle size of the first thermally conductive filler is 50.5 microns, 60 microns, 65 microns, 70 microns, 75 microns, 80 microns, 85 microns, 90 microns, 95 microns, 100 microns, and values ​​between any two of the above values.

[0044] Exemplarily, the first thermally conductive filler accounts for 40%, 45%, 50%, 55%, 60% of the organic silicon thermally conductive material, or a value between any two of the above values.

[0045] Exemplarily, the D50 particle size of the second thermally conductive filler is 10.5 microns, 15 microns, 20 microns, 25 microns, 30 microns, 35 microns, 40 microns, 45 microns, 50 microns, and values ​​between any two of the above values.

[0046] Exemplarily, the second thermally conductive filler accounts for 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% of the organic silicon thermally conductive material, and a value between any two of the above values.

[0047] Exemplarily, the D50 particle size of the third thermally conductive filler is 0.1 micron, 1 micron, 2 microns, 3 microns, 4 microns, 5 microns, 6 microns, 7 microns, 8 microns, 9 microns, 10 microns, and values ​​between any two of the above values.

[0048] Exemplarily, the third thermally conductive filler accounts for 5%, 10%, 15%, 20% of the organic silicon thermally conductive material, or a value between any two of the above values.

[0049] Exemplarily, the D50 particle size of the fourth thermally conductive filler is 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, and values ​​between any two of the above values.

[0050] Exemplarily, the fourth thermally conductive filler accounts for 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% of the silicone thermally conductive material and values ​​between any two of the above values.

[0051] Optionally, the D50 particle size of the first thermally conductive filler is 80 microns to 100 microns; the D50 particle size of the second thermally conductive filler is 30 microns to 45 microns; the D50 particle size of the third thermally conductive filler is 0.5 microns to 7 microns; the D50 particle size of the fourth thermally conductive filler is 1 nanometer to 50 nanometers. Further, the D50 particle size of the second thermally conductive filler is 35 microns to 40 microns; the D50 particle size of the third thermally conductive filler is 0.5 microns to 1 micron or 4 microns to 6 microns. In this way, it is beneficial to further improve the thermal conductivity of the organic silicon thermally conductive material in this application, and have a lower overflow rate.

[0052] In some embodiments of the present application, the thermally conductive filler consists of a first thermally conductive filler, a second thermally conductive filler, a third thermally conductive filler, and a fourth thermally conductive filler.

[0053] In some embodiments of the present application, the first thermally conductive filler, the second thermally conductive filler, the third thermally conductive filler and the fourth thermally conductive filler are independently selected from one or more of aluminum oxide, aluminum nitride, silicon oxide, zinc oxide, boron nitride and diamond. It is understandable that aluminum oxide, aluminum nitride, zinc oxide, boron nitride and diamond have high thermal conductivity, which is conducive to further improving the thermal conductivity of the organic silicon thermally conductive material in the present application.

[0054] In some embodiments of the present application, the first thermally conductive filler, the second thermally conductive filler, the third thermally conductive filler, and the fourth thermally conductive filler are all spherical or angular.

[0055] Exemplarily, the first thermally conductive filler and the second thermally conductive filler are spherical aluminum nitride, the third thermally conductive filler is spherical aluminum oxide, and the fourth thermally conductive filler is spherical aluminum oxide or spherical silicon oxide.

[0056] It should be noted that in the related art, in order to improve the thermal conductivity of the material, it is necessary to increase the proportion of thermal conductive fillers in the material as much as possible. However, the greater the proportion of thermal conductive fillers in the material, the worse the fluidity of the material, resulting in a small amount of glue dispensed, and the use scenarios are limited. For example, in some use scenarios, the thermal conductive material is required to have a high thermal conductivity and glue dispensed amount, while having a low overflow rate. How to balance the contradiction between the thermal conductivity, fluidity (such as glue dispensed amount) and overflow rate of the thermal conductive material is a difficult problem that technicians in this field need to solve urgently.

[0057] In order to further make the organic silicon thermal conductive material in this application have higher thermal conductivity and flowability, and have a lower overflow rate, the thermal conductive filler accounts for 94% to 97% of the organic silicon thermal conductive material, the first thermal conductive filler accounts for 35% to 60% of the organic silicon thermal conductive material; the second thermal conductive filler accounts for 10% to 50% of the organic silicon thermal conductive material; the third thermal conductive filler accounts for 5% to 20% of the organic silicon thermal conductive material; the fourth thermal conductive filler accounts for 0.1% to 1.4% of the organic silicon thermal conductive material. The thermal conductivity of the organic silicon thermal conductive material prepared in the embodiment of the present application is greater than 10W / mK, the dispensing amount is greater than 60g / min, the overflow rate is less than 0.1%, and it has higher thermal conductivity and flowability, and has a lower overflow rate.

[0058] It is understandable that if the filling ratio of the thermal conductive filler is too large, for example, greater than 97%, it is easy to cause its viscosity to be too large, the dispensing amount is reduced, and the process is more difficult. In this embodiment, by controlling the filling ratio in the organic silicon thermal conductive material to be between 94% and 97%, it is beneficial to make the organic silicon thermal conductive material in this application have higher thermal conductivity and dispensing amount.

[0059] It should be noted that in the related art, when the proportion of thermally conductive fillers is higher than 94%, its fluidity is generally poor, resulting in an unsatisfactory amount of thermally conductive material dispensed. In this embodiment, the first thermally conductive filler is controlled to account for 35% to 60% of the silicone thermally conductive material; the second thermally conductive filler accounts for 10% to 50% of the silicone thermally conductive material; the third thermally conductive filler accounts for 5% to 20% of the silicone thermally conductive material; and the fourth thermally conductive filler accounts for 0.1% to 1.4% of the silicone thermally conductive material. In this way, by further adjusting the distance between the thermally conductive fillers in the silicone thermally conductive material, the mobility of the silicone molecular chain is adjusted, so that the silicone thermally conductive material in this application has a higher dispense amount, thermal conductivity and a lower overflow rate, thereby achieving a balance between the thermal conductivity, fluidity (such as dispense amount) and overflow rate of the thermally conductive material.

[0060] In some embodiments of the present application, the silicone resin matrix is ​​polydimethylsiloxane. It is understandable that polydimethylsiloxane has a relatively low viscosity, which is beneficial to improving the fluidity of the organic silicon thermal conductive material in the present application.

[0061] Furthermore, the polydimethylsiloxane is a polydimethylsiloxane with a long chain branching structure. In this embodiment, the polydimethylsiloxane has a long chain branching structure, which is conducive to further making the distance between the fillers close to or smaller than the size of the molecular chain in the silicone resin matrix, thereby reducing the kinetic energy of the silicone resin and reducing the overflow rate of the silicone thermal conductive material in this application. In addition, the polydimethylsiloxane with a long chain branching structure is conducive to increasing the entanglement between polymer molecular chains and the entanglement between polymer molecular chains and thermal conductive fillers, which is conducive to further improving thermal conductivity and reducing the overflow rate.

[0062] In some embodiments of the present application, the silicone resin matrix includes vinyl terminated polydimethylpolysiloxane, polydimethylpolysiloxane with side chain silicon-hydrogen bonds, and polydimethylpolysiloxane with silicon-hydrogen terminated. It is understood that vinyl terminated polydimethylpolysiloxane can react with polydimethylpolysiloxane with side chain silicon-hydrogen bonds to generate polydimethylsiloxane with a long branched chain structure.

[0063] Furthermore, the synthesis of polydimethylpolysiloxane includes: 1 to 3 parts of vinyl-terminated polydimethylpolysiloxane; 0.2 to 1.5 parts of silicon-hydrogen-terminated polydimethylpolysiloxane; and 0.5 to 2 parts of polydimethylpolysiloxane with side chain silicon-hydrogen bonds. It should be noted that 1 to 3 parts of vinyl-terminated polydimethylpolysiloxane, that is, vinyl-terminated polydimethylpolysiloxane accounts for 1% to 3% of the organic silicon thermal conductive material. Similarly, the silicon-hydrogen-terminated polydimethylpolysiloxane accounts for 0.2% to 1.5% of the organic silicon thermal conductive material. The side chain silicon-hydrogen-bonded polydimethylpolysiloxane accounts for 0.5% to 2% of the organic silicon thermal conductive material.

[0064] Furthermore, in the present application, the viscosity of the vinyl-terminated polydimethylpolysiloxane is 50 to 500 mPa.s, and the terminal vinyl content in the vinyl-terminated polydimethylpolysiloxane is 0.5%-2%; the viscosity of the silicon-hydrogen-terminated polydimethylpolysiloxane is 10 to 100 mPa.s, and the content of silicon-hydrogen bonds in the silicon-hydrogen-terminated polydimethylpolysiloxane is 0.1%-3.0%; the viscosity of the polydimethylpolysiloxane with side chain silicon-hydrogen bonds is 10 to 100 mPa.s, and the content of silicon-hydrogen bonds in the polydimethylpolysiloxane with side chain silicon-hydrogen bonds is 0.1%-3.0%.

[0065] For example, the viscosity of the vinyl terminated polydimethylpolysiloxane is 50 mPa·s, 100 mPa·s, 200 mPa·s, 300 mPa·s, 400 mPa·s, 500 mPa·s and any value between the above two values. It should be noted that, unless otherwise specified, the viscosity in this application refers to the viscosity at room temperature (25° C.).

[0066] For example, the terminal vinyl content in the vinyl terminated polydimethylpolysiloxane is 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% and values ​​between any two of the above values. Taking the terminal vinyl content in the side chain hydrogenated polydimethylsiloxane as 1% as an example, if the side chain hydrogenated polydimethylsiloxane is 100g, the terminal vinyl content in the side chain hydrogenated polydimethylsiloxane is 1mmol accordingly.

[0067] Illustratively, the viscosity of the silicon-hydrogen terminated polydimethylpolysiloxane is 10 mPa·s, 20 mPa·s, 30 mPa·s, 40 mPa·s, 50 mPa·s, 60 mPa·s, 70 mPa·s, 80 mPa·s, 90 mPa·s, 100 mPa·s, and values ​​between any two of the above values.

[0068] Exemplarily, the content of silicon-hydrogen bonds in the silicon-hydrogen terminated polydimethylpolysiloxane is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3% and values ​​between any two of the above values. Taking the content of silicon-hydrogen bonds in the side chain hydrogen-containing polydimethylsiloxane as 0.1% as an example, if the side chain hydrogen-containing polydimethylsiloxane is 100g, correspondingly, the content of silicon-hydrogen bonds in the side chain hydrogen-containing polydimethylsiloxane is 0.1mmol.

[0069] Exemplarily, the viscosity of the polydimethylpolysiloxane with side chain silicon-hydrogen bonds is 10 mPa·s, 20 mPa·s, 30 mPa·s, 40 mPa·s, 50 mPa·s, 60 mPa·s, 70 mPa·s, 80 mPa·s, 90 mPa·s, 100 mPa·s, and values ​​between any two of the above values.

[0070] Exemplarily, the content of silicon-hydrogen bonds in the polydimethylpolysiloxane with side chain silicon-hydrogen bonds is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3% and values ​​between any two of the above values. Taking the silicon-hydrogen bond content of the side chain hydrogen-containing polydimethylsiloxane as 0.1% as an example, if the side chain hydrogen-containing polydimethylsiloxane is 100g, correspondingly, the silicon-hydrogen bond content of the side chain hydrogen-containing polydimethylsiloxane is 0.1mmol.

[0071] In some embodiments of the present application, the silicone resin matrix further comprises a hydrosilylation reaction catalyst. For example, the catalyst includes but is not limited to a platinum catalyst. Further, the catalyst is selected from at least one of a Spier catalyst and a Custer catalyst.

[0072] In some embodiments of the present application, the mass percentage of the catalyst in the organic silicon thermal conductive material is 0.1% to 2%. Exemplarily, the mass percentage of the catalyst in the organic silicon thermal conductive material is 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2% and values ​​between any two of the above values.

[0073] In some embodiments of the present application, the silicone resin matrix further includes a hydrosilylation reaction inhibitor. Exemplarily, the inhibitor includes but is not limited to at least one of acetylene compounds, ene-yne ​​compounds, and methylvinylcyclosiloxane.

[0074] Furthermore, the acetylene compound includes at least one of 2-methyl-3-butyn-2-ol and 3-phenyl-1-butyn-3-ol.

[0075] Further, the ene-yne ​​chemical includes at least one of 3-methyl-3-pentene-1-yne and 3,5-dimethyl-3-hexene-1-yne.

[0076] Further, the methylvinylcyclosiloxane includes 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane.

[0077] In some embodiments of the present application, the inhibitor accounts for 0.1% to 0.5% by mass of the organic silicon thermal conductive material. Exemplarily, the catalyst accounts for 0.1%, 0.2%, 0.3%, 0.4%, 0.5% by mass of the organic silicon thermal conductive material, and a value between any two of the above values.

[0078] In some embodiments of the present application, the organic silicon thermal conductive material further includes a filler modifier, and the mass percentage of the filler modifier in the organic silicon thermal conductive material is 1% to 5%. Exemplarily, the mass percentage of the filler modifier in the organic silicon thermal conductive material is 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, and a value between any two of the above values.

[0079] Furthermore, the filler modifier is a silane coupling agent. For example, the filler modifier is at least one of n-decyltrimethoxysilane and dodecyltrimethoxysilane.

[0080] The second aspect of the embodiment of the present application further provides an optical module, the optical module includes the above-mentioned organic silicon thermal conductive material. Exemplarily, the optical module also includes an optical transceiver module and a heat sink housing, and the organic silicon thermal conductive material is filled between the optical transceiver module and the heat sink housing. In this way, the heat generated by the optical transceiver module can be quickly transferred to the heat sink housing through the organic silicon thermal conductive material for heat dissipation, thereby improving the heat dissipation effect of the optical transceiver module.

[0081] The organic silicon thermal conductive material in the present application is further described below in conjunction with specific embodiments and test results.

[0082] Table 1 Experimental example raw materials

[0083]

[0084]

[0085] Example 1 to Example 14

[0086] A certain amount of silicone resin matrix (polydimethylpolysiloxane composition) is added to a container, a first filler is added to the container, and a high-speed mixer is used to mix at 800RPM for 20 seconds, then a second filler is added and mixed at 1000RPM for 20 seconds, a third filler is added and mixed at 1500RPM for 20 seconds, and a fourth filler is added and mixed at 2500RPM for 20 seconds, followed by manual mixing. After the silicone resin matrix and the thermally conductive filler are evenly mixed, an inhibitor and a catalyst are added thereto, and mixed at 800RPM for 10 seconds to obtain a silicone thermally conductive material. The obtained silicone thermally conductive material is heated to 100°C and maintained at 100°C for 1H to obtain a test sample. The specific components are shown in Table 2.

[0087] Comparative Example 1

[0088] A certain amount of silicone resin matrix (polydimethylpolysiloxane composition) is placed in a container, a first filler is added to the container, and a high-speed mixer is used to mix at 800RPM for 20 seconds, then a second filler is added and mixed at 1000RPM for 20 seconds, and then a third filler is added and mixed at 1500RPM for 20 seconds, followed by manual mixing. After the silicone resin matrix and the thermally conductive filler are evenly mixed, an inhibitor and a catalyst are added thereto, and mixed at 800RPM for 10 seconds to obtain an organic silicon thermally conductive material. The obtained organic silicon thermally conductive material is heated to 100°C and maintained at 100°C for 1H to obtain a test sample. The specific components are shown in Table 2.

[0089] The difference between Comparative Example 1 and Example 1 is that the fourth filler is not added in Comparative Example 1.

[0090] Experimental testing

[0091] Thermal conductivity characterization: Thermal conductivity was determined according to ASTM D5470-06 using a thermal resistance and thermal conductivity measuring device. The cured sample was applied between a hot plate and a cold plate. A pressure of 275.8 kPa (40 psi) was applied to keep the sample in contact with the plate. Thermal resistance was measured at different bonding layer thicknesses (BLT) (1.0 mm / 2.0 mm / 3.0 mm). Thermal conductivity was calculated by K=10 / slope by fitting a linear equation to thermal impedance and BLT.

[0092] Dispensing volume characterization: The extrusion rate of the sample is determined using a peach dispensing machine. The sample material is loaded into a 30 cubic centimeter syringe with a 2.54 millimeter (mm) opening. The sample is dispensed through the opening by applying a pressure of 0.62 MPa to the syringe. The mass of the sample in grams (g) extruded after one minute is the dispensing volume.

[0093] Characterization of small molecule overflow rate: Weigh the sample to obtain its initial weight M1, and pad filter paper on both sides of the sample (the sample stacking structure from bottom to top is: tin foil, filter paper, sample, filter paper, aluminum foil). Place the prepared sample on an aluminum plate, and control the compression of the material to between 40% and 50% by placing metal gaskets of different thicknesses on the four corners of the aluminum plate. Then cover it with another aluminum plate, screw it, and tighten the nut to ensure that the material under test cannot move on the aluminum plate. The assembled test fixture is placed in an 85°C constant temperature oven. At the same time, place a sample of the material under test in a glass watch dish as a control group, weigh the mass change of the glass dish + the material under test before and after baking, and test the volatile mass m of the material under test. Take out the test fixture after 24 hours after it is placed in the oven, wait for it to cool down and put it in a dryer, wait until it reaches room temperature, weigh the weight of the sample and filter paper M2, wipe off the residual sample on the filter paper, weigh the filter paper M3, calculate its weight loss rate, and measure the oil halo diameter. Data processing: Oil bleeding = (M2-M3-m) / M1*100%.

[0094] The samples prepared in each experimental example were tested for thermal conductivity, dispensing amount and overflow rate, and the test results are shown in Table 2.

[0095] Table 2 Components of each experimental example and comparative example

[0096]

[0097]

[0098] Table 3 Test results of each experimental example

[0099] Overflow rate (%) Dispensing amount (g / min) Thermal conductivity (W / mK) S1 0.05 61.0 12.35 S2 0.06 71.1 11.12 S3 0.08 75.0 10.52 S4 0.09 62.5 11.50 S5 0.04 62.4 12.00 S6 0.07 66.4 11.43 S7 0.06 5.8 12.34 S8 0.06 12.3 9.47 S9 0.04 41.0 10.45 S10 0.05 56.0 11.56 S11 0.05 48.0 11.21 S12 0.06 40.2 10.86 S13 0.05 54.0 11.10 S14 0.03 38.0 11.20 D1 0.25 53.0 11.45

[0100] It can be seen from Examples 1 to 14 and Comparative Example 1 that in the present application, by adding thermally conductive fillers to the silicone resin matrix, adding 0.1% to 2% of thermally conductive fillers below 100 nanometers to the organic silicon thermal conductive material, it is beneficial to reduce the overflow rate of the organic silicon thermal conductive material. The possible reason is that the addition of thermally conductive fillers below 100 nanometers can greatly reduce the distance between fillers in the organic silicon thermal conductive material, and can make the molecular chain size of the organic silicon resin larger than or close to the distance between fillers, thereby producing a confinement effect, reducing the kinetic energy of the organic silicon resin, and is beneficial to reducing the overflow rate of the organic silicon thermal conductive material in the present application.

[0101] By comparing Examples 1 to 6 and Examples 9 to 14 with Example 7, it can be seen that when the mass fraction of the fourth thermally conductive filler in the organic silicone thermally conductive material is about 1.4 parts, the thermal conductivity of the organic silicone thermally conductive material is relatively high, but the glue dispensing amount is too low.

[0102] By comparing Examples 1 to 6 and Examples 9 to 14 with Example 8, it can be seen that when the mass fraction of the thermally conductive filler in the organic silicon thermally conductive material is less than 92 parts, the thermal conductivity of the organic silicon thermally conductive material is less than 10 W / mK. When the mass fraction of the thermally conductive filler in the organic silicon thermally conductive material is between 93.5 parts and 96.5 parts, the thermal conductivity of the organic silicon thermally conductive material is higher than 10 W / mK.

[0103] By comparing Examples 1 to 6 with Examples 7 to 14, it can be seen that when the mass fraction of thermally conductive filler added to the silicone thermally conductive material is 94 to 97 parts, and the mass fraction of the fourth thermally conductive filler is between 0.4 and 1 parts, and the first thermally conductive filler accounts for 35% to 60% of the silicone thermally conductive material; the second thermally conductive filler accounts for 10% to 50% of the silicone thermally conductive material; and the third thermally conductive filler accounts for 5% to 20% of the silicone thermally conductive material, the thermal conductivity of the silicone thermally conductive material is not less than 10 W / mK, the dispensing amount is greater than 60 g / min, the overflow rate is less than 0.1%, and it has a low overflow rate as well as a high dispensing amount and thermal conductivity.

[0104] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. An organic silicon thermal conductive material, comprising a silicone resin matrix and a thermal conductive filler; The thermally conductive filler comprises a first thermally conductive filler, a second thermally conductive filler, a third thermally conductive filler and a fourth thermally conductive filler; calculated by mass ratio, the thermally conductive filler accounts for more than 90% of the organic silicon thermally conductive material, and the first thermally conductive filler accounts for 30% to 65% of the organic silicon thermally conductive material; The second thermally conductive filler accounts for 5% to 55% of the organic silicon thermally conductive material; The third thermally conductive filler accounts for 1% to 30% of the organic silicon thermally conductive material; the fourth thermally conductive filler accounts for 0.1% to 2% of the organic silicon thermally conductive material; Among them, the D50 particle size of the first thermally conductive filler is 50.5 microns to 100 microns; the D50 particle size of the second thermally conductive filler is 10.5 microns to 50 microns; the D50 particle size of the third thermally conductive filler is 0.1 microns to 10 microns; and the D50 particle size of the fourth thermally conductive filler is 100 nanometers or less.

2. The organic silicon thermally conductive material according to claim 1, characterized in that: The thermally conductive filler accounts for 94% to 97% of the thermally conductive silicone material; and / or The first thermally conductive filler accounts for 35% to 60% of the organic silicon thermally conductive material; the second thermally conductive filler accounts for 10% to 50% of the organic silicon thermally conductive material; The third thermally conductive filler accounts for 5% to 20% of the organic silicon thermally conductive material; The fourth thermally conductive filler accounts for 0.1% to 1.4% of the organic silicon thermally conductive material.

3. The organic silicon thermally conductive material according to claim 1 or 2, characterized in that: The first thermally conductive filler, the second thermally conductive filler, the third thermally conductive filler and the fourth thermally conductive filler are independently selected from one or more of aluminum oxide, aluminum nitride, silicon oxide, zinc oxide, boron nitride and diamond.

4. The organic silicon thermally conductive material according to claim 3, characterized in that: The first thermally conductive filler, the second thermally conductive filler, the third thermally conductive filler and the fourth thermally conductive filler are independently spherical or angular.

5. The organic silicon thermal conductive material according to claim 1, characterized in that: The thermally conductive filler consists of the first thermally conductive filler, the second thermally conductive filler, the third thermally conductive filler and the fourth thermally conductive filler.

6. The organic silicon thermal conductive material according to claim 1, characterized in that: The silicone resin matrix includes polydimethylsiloxane having a long-chain branched structure; or The silicone resin matrix includes vinyl terminated polydimethylpolysiloxane, side chain silicon-hydrogen bonded polydimethylpolysiloxane and silicon-hydrogen terminated polydimethylpolysiloxane; and / or The organic silicon thermal conductive material further comprises at least one of a filler modifier, a catalyst, and an inhibitor; and / or The dispensing amount of the organic silicon thermal conductive material is greater than or equal to 60g / min; and / or The thermal conductivity of the organic silicon thermal conductive material is greater than or equal to 10W / mK; and / or The overflow rate of the organic silicon thermal conductive material is less than or equal to 0.1%.

7. The organic silicon thermal conductive material according to claim 6, characterized in that: The viscosity of the vinyl-terminated polydimethylpolysiloxane is 50 to 500 mPa.s, and the terminal vinyl content of the vinyl-terminated polydimethylsiloxane is 0.5% to 2%; and / or The viscosity of the silicon-hydrogen terminated polydimethylpolysiloxane is 10 to 100 mPa.s, and the content of silicon-hydrogen bonds in the silicon-hydrogen terminated polydimethylpolysiloxane is 0.1% to 3.0%; and / or The viscosity of the polydimethylpolysiloxane with side chain silicon-hydrogen bonds is 10 to 100 mPa.s, and the content of silicon-hydrogen bonds in the polydimethylpolysiloxane with side chain silicon-hydrogen bonds is 0.1% to 3.0%; and / or Calculated by mass ratio, the vinyl-terminated polydimethylpolysiloxane accounts for 1% to 3% of the silicone thermal conductive material; the silicon-hydrogen-terminated polydimethylpolysiloxane accounts for 0.2% to 1.5% of the silicone thermal conductive material; and the side chain silicon-hydrogen bonded polydimethylpolysiloxane accounts for 0.5% to 2% of the silicone thermal conductive material.

8. The organic silicon thermal conductive material according to claim 6, characterized in that: The filler modifier comprises an alkyltrialkoxysilane coupling agent; and / or The catalyst comprises at least one of a Spier catalyst and a Custer catalyst; and / or The mass percentage of the catalyst in the organic silicon thermal conductive material is 0.1% to 2%; and / or The inhibitor comprises at least one of acetylene compounds, ene-yne ​​compounds, and methylvinylcyclosiloxane; and / or The inhibitor accounts for 0.1% to 0.5% by mass of the organic silicon thermal conductive material; and / or The filler modifier accounts for 1% to 5% by mass of the organic silicon thermal conductive material.

9. The organic silicon thermal conductive material according to claim 8, characterized in that: The alkyltrialkoxysilane coupling agent includes at least one of n-decyltrimethoxysilane and dodecyltrimethoxysilane.

10. An optical module, characterized in that: The optical module comprises the organic silicon thermal conductive material according to any one of claims 1 to 9.